EFFECTIVENESS OF MODERN REHABILITATION METHODS IN ORTHOPEDIC DISEASES (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Modern rehabilitation methods play a crucial role in the management and recovery of patients with orthopedic diseases. This study examines the effectiveness of contemporary rehabilitation approaches, including physiotherapy, telerehabilitation, prehabilitation, and multidisciplinary interventions. A systematic review of recent literature and clinical findings indicates that modern rehabilitation significantly improves functional outcomes, reduces pain, enhances quality of life, and accelerates recovery in orthopedic patients. However, variability in methodologies and patient characteristics affects the consistency of results. The findings highlight the importance of individualized rehabilitation protocols and integration of innovative technologies.